We are inevitable - Forman, Gayle (Viking, 2021)
After losing his brother, mom, and most of his friends, Aaron Stein is left with his shambolic father alone in their moldering secondhand bookstore, but just when he considers selling the store he meets new people and takes on new challenges, helping him come to terms with what he has lost and who he wants to be.